The answer is supposed to be -2(e^x - e^-x)/(e^x + e^-x)^2 but I’m not sure how to get there because my answer always ends up as -2(e^x + e^-x)/(e^x+e^x)^2, so I’m not sure where I’m missing the negative or if the answer key has a typo.

The answer is supposed to be 2ex exex ex2 but Im not sure how to get there because my answer always ends up as 2ex exexex2 so Im not sure where Im missing the n class=

Respuesta :

Answer:

The answer to your question is below

Step-by-step explanation:

Derivative of a quotient  

                      [tex]\frac{df(x)}{dg(x)} = \frac{f'(x)g(x) - g'(x)f(x)}{g^{2}(x) }[/tex]

f'(x) = 0

g'(x) = [tex]e^{x} - e^{-x}[/tex]

g²(x) = ([tex](e^{x} + e^{-x} )^{2}[/tex]

Substitution

[tex]\frac{df(x)}{dg(x)} = \frac{0(e^{x} + e^{-x)} - 2(e^{x}- e^{-x)}}{(e^{x}+ e^{-x})^{2}  }[/tex]

Simplification and result

[tex]\frac{df(x)}{dg(x)} = \frac{-2(e^{x} - e^{-x})}{(e^{x}+ e^{-x} )^{2}  }[/tex]